The Impact of Gamification in Digital Learning Media on Student Participation in Citizenship Subjects - Kristiawan, Indria; Hariati, Tunik (Electronic Journal of Education, Social Economics and Technology, 2024)
This study aims to analyze the impact of gamification in digital learning media on student participation in the subject of Civic Education. The research method used is a quantitative method with a descriptive approach. Data was collected through observations, interviews, and questionnaires involving students and teachers as respondents. The data analysis techniques used include descriptive statistical analysis to measure the level of student participation and qualitative analysis to understand the experiences of students and teachers in the application of gamification. The results showed that gamification elements, such as points, challenges, and leaderboards, significantly increased student motivation and engagement in learning. Collaborative-based challenges are a major factor that encourages interaction between students, while the reward system provides an additional motivational boost. However, there are several obstacles in implementation, such as limited access to technology and the readiness of educators in managing gamification. Therefore, a more adaptive development strategy is needed to optimize the use of gamification in civic learning.